The Ashley book of knots - Ashley, Clifford Warren, 1881-1947 (Faber and Faber Limited, 1947)
"The variety of the subject is amazing. No less than 3,854 knots and splices, hitches and hooks, beckets and toggles, sinnets and so on are described and illustrated."--BOOK COVER.